“What’s Past is Prologue”: Postcolonialism, Globalisation, and the Demystification of Shakespeare in Malaysia - Kok, Su Mei (SARE: Southeast Asian Review of English, 2017)
Since 2011, Shakespeare Demystified, a series of productions with a pedagogical focus, has been transforming the landscape of Shakespearean performances in Malaysia. It is the closest Malaysia currently has to a regular Shakespeare season and the actors behind it comprise the only theatrical group committed to bringing Shakespeare to the stage. But Shakespeare Demystified continues a long Malaysian tradition of performing Shakespeare for educational purposes, which traces its origins to colonial Malaya. This paper examines the cultural significances of Shakespeare Demystified, locating it within the history and development of English-language Shakespearean performances in Malaysia while attending to recent shifts in local engagements with the Bard as result of the increasing globalisation of education.